Differences in spatial patterns of long-term care depending on severity in Hokkaido, Japan - Kazuki Ohashi (Geospatial Health, 2022)
The increasing demand for long-term care (LTC) among the ageing population is a serious problem worldwide, which has greatly increased also in Japan since the introduction of the LTC insurance system there. Since there is a difference between insurers with respect to the proportion of people needing LTC, this study aimed at clarifying the spatial patterns of LTC. Insurer (n=156) LTC data for the period 2012-2019 were obtained from Ministry of Health, Labour, and Welfare and those needing LTC were classified into three classes: total, mild and severe with ageand sex-adjusted proportions needing LTC. Global and local Moran’s I statistics were calculated for each 2-year period to clarify the trends of global and local spatial clusters. From 2012 to 2019, the mean proportion of mild class cases increased (10.6% to 11.6%), whereas that of severe class cases decreased slightly (5.9% to 5.7%). The spatial pattern of the proportion of each class revealed positive spatial autocorrelation. Based on analysis by local Moran’s I, differences in spatial patterns were emphasised between the mild and severe classes. In Hokkaido, High-High clusters of mild cases were identified in the central and southern parts and severe ones in the northern and southern parts. Spatial patterns differed depending on the LTC class. Some insurers had distinctly higher or lower certification rates than those of their neighbourhoods.